THE ROLE OF COMMUNITY-BASEDCHILDREN PROTECTION ACTIVIST (PATBM) IN THE CHILD PROTECTION - Ms dianawati (IKIP Siliwangi Bandung, 2018)
AbstractThis study based on the number of cases of child abuse, the exploitation of children to be employed as a seller of